LEGAL PROTECTION POLICY FOR VICTIMS OF ONLINE FRAUD IN LANGSA CITY - Azmi Saputra; Azmiati Zuliah; Andi Maysarah (NOMOI Law Review, 2026)
The rapid advancement of digital technology has precipitated a surge in online fraud, necessitating robust legal mechanisms to protect vulnerable consumers. This research aims to analyze the regulatory framework governing legal protection for fraud victims in Indonesia and evaluate its implementation by law enforcement in Langsa City. Employing an empirical juridical method, this study utilizes data from interviews with police officials and victims to assess the discrepancy between normative laws and empirical reality. The discussion reveals that while the Criminal Code and ITE Law provide a normative foundation, practical application is obstructed by structural barriers, including inadequate digital forensic infrastructure, limited human resource capacity, and the cross-jurisdictional nature of cybercrime. Consequently, the restitution of victims' financial losses remains difficult to achieve despite the use of restorative justice mechanisms. The study concludes that legal protection in Langsa City is currently suboptimal due to these technical and resource limitations. It is suggested that law enforcement agencies enhance their technical capacity and cross-sectoral coordination, while simultaneously promoting public digital literacy to create a more resilient and just digital ecosystem.